How Does Management Equity Work in MSME’s? (A MSME’s Level Approach) - Lestari, Made Irma (Department of Accounting-Faculty of Economic and Business (FEB), 2023)
This exploratory study with a qualitative approach aims to provide an overview about the condition of micro, small, and medium enterprises (MSMEs) in Indonesia regarding the concept of equity management based on the economic entity assumption. Whereas equity (owner's capital and operating profit) is the acquisition of funds of the business that must be separated from the private entity that owns the funds. Research data are primary data obtained by in-depth interviews and direct observation. Guided by the latest regulation, PP Nomor 7 Tahun 2021 concerning the Ease, Protection, and Empowerment of Koperasi and Micro, Small, and Medium Enterprises, researcher received responses from five business actors, each representing micro, small, and medium enterprises. This study found that the response of business actors at the micro, small, and medium levels was quite good about the awareness of separating business equity from private equity. However, in practice, the practice of equity management is proportional to the level of business, which means that the higher the level of business, the better the implementation of equity management that can be done. Implementation of equity management in small and medium enterprises is better than micro enterprises. With the enactment of PP Nomor 7 Tahun 2021, the government has expressed a commitment to raise micro-enterprises to the advance level. Thereby from this research, it is hoped that the government can make the issue of equity management in MSMEs as focus of regular guidance and assistance, especially for micro-enterprises.